1980
DOI: 10.1093/rheumatology/19.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Foot Function in Juvenile Chronic Arthritis

Abstract: Measurement of the force distribution under the foot has been used to assess the effect of juvenile chronic arthritis on foot function. The results obtained from the feet of eight patients were compared with the feet of 11 normal children. The peak forces and contact times were measured for functional areas of the foot. When considered as a group, the patients had significantly reduced loading under all the toes and the two medial metatarsal heads, and increased contact time for the heel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Dhanendran et al [8] evaluated force distribution under the foot of the JRA patient and observed significantly reduced loading under the toes and the two medial metatarsal heads, as well as increased heel contact time, compared with healthy children. Witemeyer et al [9] studied the time-distance variables of the gait pattern of children with JRA and found that those with severe joint disability suffered marked deviations from normal gait; the degree of disability and specific gait deviations, however, were not described.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dhanendran et al [8] evaluated force distribution under the foot of the JRA patient and observed significantly reduced loading under the toes and the two medial metatarsal heads, as well as increased heel contact time, compared with healthy children. Witemeyer et al [9] studied the time-distance variables of the gait pattern of children with JRA and found that those with severe joint disability suffered marked deviations from normal gait; the degree of disability and specific gait deviations, however, were not described.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evaluation scales have traditionally included data thought to be clinically important to the investigator. 4,5,7,9,10,11,13,15,16,18,19,20,22,24,25 These measurements for the foot and ankle have focused on range of motion, pain, function and radiographic criteria. These data may be given either numeric values and composite totals or categorical scores, both of which suggest excellent, good, fair, or poor results.…”
Section: Introductionmentioning
confidence: 99%
“…1). La douleur est souvent mod6r6e, la g6ne fonctionnelle minime, mais une boiterie, ou une marche en rotation externe peut 6tre d6cel6e ~ un examen attentif [4]. La limitation du jeu articulaire est constante.…”
Section: Une ~Volution Insidieuseunclassified